Tracing the Behavioral Roots: Determinants of Open Defecation Practices - Desi Mustika Wati; Yuanita Windusari; Nur Alam Fajar (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Open Defecation (OD) remains a persistent environmental health issue in many regions, particularly in low-income and developing countries. This behavior contributes to increased risks of environmentally related diseases, parasitic infections, and reduced quality of life. Numerous studies indicate that OD practices are influenced not only by environmental factors but also reflect demographic, social, economic, cultural, and sanitation-service conditions. This study aims to examine the determinants of OD behavior through a comprehensive literature review and to identify consistent patterns of significant associations reported in recent research. Methods: A literature review was conducted on 30 research articles examining OD determinants, retrieved from Google Scholar, PubMed, ScienceDirect, and Garuda, with publication years ranging from 2021 to 2025. The analysis was guided by a behavioral framework encompassing three groups of factors: predisposing, enabling, and reinforcing factors. Data were synthesized based on the significance of associations, frequency of variable occurrence, and consistency of findings across studies. Results: Predisposing factors emerged as the dominant determinants of OD behavior, particularly education level (63%), knowledge (53%), and attitude (50%). Most variables within this category showed significant associations, especially knowledge, attitude, and education level (>70% of the studies). Enabling factors, including latrine availability (33%) and water availability (27%), also played key roles, with most studies reporting significant relationships concerning basic sanitation infrastructure. Reinforcing factors, such as social support and the role of health workers, were identified as important determinants, contributing significantly in more than 70% of the reviewed studies. Overall, OD behavior was found to result from a complex interaction of individual, environmental, and social dimensions. Conclusion: Efforts to reduce open defecation must integrate multidimensional approaches that include improving sanitation literacy through education, providing adequate and sustainable sanitation facilities, and strengthening the role of community leaders and health workers in promoting hygienic behavior. Further research is recommended to evaluate the effectiveness of community-based interventions and to explore behavioral changes in the context of socio-economic dynamics.